Development of a DNA biosensor based on magnetic nanoparticles for the detection of Ganoderma boninense - Hushiarian, Roozbeh (2015)
The unique electrochemical and optical properties of nanoparticles combined with the relative ease with which their shape and size can be controlled is currently showing promise in the development of new biosensors. In particular, magnetic nanoparticles are of great interest in DNA sensors for their ability to both separate biological macromolecules as well as to optimize DNA hybridization. The intent of this research was to address the gap in knowledge about the fundamentals of the molecular interactions between DNA and nanoparticles, especially magnetic nanoparticles. The pathogen selected was the basidiomycete Ganoderma boninense, the main cause of basal stem rot disease which continues its devastating effect on oil palm trees in South East Asia. A designed DNA sequence and its complementary strains – a sequence of 18s rRNA gene of Ganoderma boninense - was taken as the template. The work in this thesis was built on understood mechanisms from previous studies with the goal of further optimizing a DNA biosensor. One major part of the research involved the design and construction of an optical magnetic nanoparticle–based biosensor using quantum dots as markers. This clearly demonstrated that DNA can bind to the surface of iron oxide nanoparticles and that they can act as effective biomolecule carriers. The detection limit of the designed optical nanosensor was calculated as 2.19×10-9 M. The sensitivity of the system was increased by 20% using a two step hybridization method. A new innovative software package was used to better understand the mechanism of detection. The other major section introduced an electrochemical method for sensing and conclusively showed that it could bring a representative sequence of an analyte to the biorecognition surface. The electrochemical sensor based on magnetic nanoparticles showed a sensitivity of 1.1×10-16 M and then this method was further extended to successfully increase the selectivity of this system by the novel use of DNA ligase. The indirect detection of the target DNA using DNA ligase was successfully performed with a detection limit of 5.37×10-14 M. This creative ligation-based mechanism was ultimately employed to detect the extracted genomic DNA of the pathogen. The methods and results in this study enhance the understanding of molecular interactions between DNA and nanoparticles and contribute to the body of work attempting to address the outstanding issue of improving the selectivity and sensitivity of DNA biosensors.